2014 UKSim-AMSS 16th International Conference on Computer Modelling and Simulation 2014
DOI: 10.1109/uksim.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Upgraded Firefly Algorithm for Portfolio Optimization Problem

Abstract: Portfolio selection is a well-known intractable research problem in the area of economics and finance. There are many definitions of the problem that by introduction of additional constraints try to make it closer to the realword conditions. Firefly algorithm is one of the latest swarm intelligence metaheuristics that was very successfully applied to both, unconstrained and constrained hard optimization problems. In this paper we adjusted firefly algorithm to the portfolio optimization problem and since the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The stated goal of this work was to improve the quality of solutions of firefly algorithm for the mentioned problem. Ultimately, these modifications resulted in a significant improvement in the results of the firefly algorithm for portfolio optimization problems [34].…”
mentioning
confidence: 99%
“…The stated goal of this work was to improve the quality of solutions of firefly algorithm for the mentioned problem. Ultimately, these modifications resulted in a significant improvement in the results of the firefly algorithm for portfolio optimization problems [34].…”
mentioning
confidence: 99%
“…Portfolio optimization can be expressed as a mean-variance problem which belongs to the group of quadratic mixed-integer programming problems. In [106,107], firefly algorithm has been extended with the use of rounding function and constraint handling approach. Deb's method [108] is also used for constraint handling.…”
Section: Modifications For Mixed Optimization Problemsmentioning
confidence: 99%
“…The authors developed these to address unconstrained portfolio optimization as well as portfolios with cardinality and bounding constraints. However, because the results were satisfactory at most even after modifications, the authors hybridized FA and ABC by incorporating the FA's search strategy into ABC to enhance exploitation and found that their data suggested superiority of the methodology compared to GA, SA, TS, and PSO [30] for unconstrained and cardinality-constrained portfolios. Streichert et al [27] account for further constraints, namely buy-in thresholds (acquisition prices) and roundlots (smallest volume of an asset that can be purchased).…”
Section: The Multi-objective Portfolio Optimization Problemmentioning
confidence: 99%